2017
DOI: 10.1111/jpn.12826
|View full text |Cite
|
Sign up to set email alerts
|

Milk fatty acid profile from cows fed with mixed rations and different access time to pastureland during early lactation

Abstract: Milk fatty acid (FA) profiles were determined in Holstein cows (n = 27) fed total mixed rations (TMR) ad libitum (G0) or diet composed by TMR (50% dry matter [DM] offered) plus grazing of pasture with 6 hr of access time to paddock in one session (G1) or 9 hr in two sessions (G2) at 45 days in milk (DIM). Moreover, milk FA was determined at 65 DIM when G0 cows turned out to G1 diet without adaptation period (Post-G0), G1 remained as controls. Milk FA was quantified using gas chromatography and mass spectrometr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
8
15
0
Order By: Relevance
“…Pasture‐based dairy systems have productive advantages compared with confinement systems, such as low production costs and improvements in milk quality, e.g. : fatty acid profile (Barca et al, ; Bargo, Delahoy, Schroeder, Baumgard, & Muller, ; White, Benson, Washburn, & Green, ; White et al, ) and industrialization products, such as cheeses (Martin, Verdier‐Metz, Buchin, Hurtaud, & Coulon, ). From the animal welfare point of view, pasture‐based dairy systems are considered a natural environment for dairy cattle (Clutton‐Brock, ) since it allows the expression of the normal behavior of the species, such as grazing (Olmos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pasture‐based dairy systems have productive advantages compared with confinement systems, such as low production costs and improvements in milk quality, e.g. : fatty acid profile (Barca et al, ; Bargo, Delahoy, Schroeder, Baumgard, & Muller, ; White, Benson, Washburn, & Green, ; White et al, ) and industrialization products, such as cheeses (Martin, Verdier‐Metz, Buchin, Hurtaud, & Coulon, ). From the animal welfare point of view, pasture‐based dairy systems are considered a natural environment for dairy cattle (Clutton‐Brock, ) since it allows the expression of the normal behavior of the species, such as grazing (Olmos et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…One of the characteristics of grazed herbage is that it contains high concentrations of n-3 FA, particularly C18:3n-3 acids within the lipids. These FA generally lead to an increased level of PUFA in milk (Elgersma, 2015;Barca et al, 2017). The nutritive value of the pre-grazing herbage of the present study can be considered high and representative of permanent swards used in Chile for feeding grazing dairy cows (Pulido et al, 2009;Keim et al, 2014).…”
Section: Discussionmentioning
confidence: 80%
“…Feeding strategies can alter milk FA composition in dairy cows fed total mixed rations or grazed herbage (Doreau et al, 2011;Elgersma, 2015, Barca et al, 2017. Generally, grazing dairy cows have greater concentrations of polyunsaturated fatty acid (PUFA) and conjugated linoleic acid (cis-9, trans 11; CLA) in the milk than cows fed total mixed rations (Elgersma, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For example, pasture‐fed versus maize silage‐based TMR‐fed cows generally produce milk fat with increased concentrations of 18:3 n‐3, C18:2 c9,t‐11, C18:1 t11, C18:1 n‐9 and C18:0, with decreasing concentrations of C12:0, C14:0 and C16:0 (Dewhurst et al, ). Other studies that have also incorporated a period of grazing with TMR feeding have also reported increases in the C18:3 n‐3 concentration of milk fat (Barca et al, ; Morales‐Almaráz et al, ; Vibart et al, ). In the current study, there was an increase of C18:3 n‐3 by approximately 29% in the milk fat of cows with a 6‐hr grazing period compared to TMR‐only cows, although the amount was still comparatively small at less than 0.5% of the total fat content.…”
Section: Discussionmentioning
confidence: 94%
“…For example, grazing dairy cows for part of the day can lower farm expenses and increase profit in scenarios with high feed costs and low milk prices (Tozer, Bargo, & Muller, )⁠ and reduce the methane output of animals (Dall‐Orsoletta, Almeida, Carvalho, Savian, & Ribeiro‐Filho, ; Mufungwe et al, )⁠. Grazing may also increase the concentration of fatty acids (FA) in milk that are beneficial to human health (Barca et al, ; Mufungwe et al, ) and, because cows can exhibit motivation to be outside at pasture (Motupalli, Sinclair, Charlton, Bleach, & Rutter, )⁠, pasture access allows natural behaviour to be expressed which may potentially improve animal welfare. Some farmers in European countries such as the United Kingdom (UK), the Netherlands and Germany are currently incentivized by milk companies to graze milking cows for a minimum of 6 hr per day, while in Scandinavia, legislation requires cows to have outdoor access for at least 6 hr per day during the summer months.…”
Section: Introductionmentioning
confidence: 99%